2022
DOI: 10.1007/s11419-022-00614-0
|View full text |Cite
|
Sign up to set email alerts
|

Histological paraffin-embedded block: a good alternative specimen to detect the use of opiates at least 20 years ago

Abstract: Purpose Since the solely certain remnants of a performed autopsy are formalin-fixed paraffin-embedded (FFPE) samples, stored in the archives of every institute of legal medicine, we managed to extract molecules of toxicological interest from these specimens. Methods We assessed the analysis of ten fresh liver samples collected from heroin-related deaths and then histologically processed the same samples. The embedded blocks were then extracted by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…2) PaCO 2 : After surgery, the breathing depth and rate may change, causing PaCO 2 to rise or fall. An increase in PaCO 2 may reflect abnormal lung function and poor ventilation, whereas a decrease in PaCO 2 may indicate accelerated tissue metabolism and respiratory compensation [ 27 ]. 3) PaO 2 : After surgery, tissue oxygen consumption may change, leading to the reduction in PaO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…2) PaCO 2 : After surgery, the breathing depth and rate may change, causing PaCO 2 to rise or fall. An increase in PaCO 2 may reflect abnormal lung function and poor ventilation, whereas a decrease in PaCO 2 may indicate accelerated tissue metabolism and respiratory compensation [ 27 ]. 3) PaO 2 : After surgery, tissue oxygen consumption may change, leading to the reduction in PaO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the details of the procedure are not explained, and it is not specified whether only one swab was used for both DNA and toxicological analyses [1]. Other studies have shown that it is possible to combine two different forensic disciplines on paraffin-embedded blocks: these substrates have been used to perform both DNA [2] and toxicological investigations [3][4][5][6] as well as proteomics [7] and western-blot studies [8]. However, no studies reported the combination of DNA investigations and toxicological analyses when only a single sample is available.…”
Section: Introductionmentioning
confidence: 99%